The utilization of plastic (PET) as coarse aggregate reinforment in concrete - Wan Nor Affidah Wan Mohd Fakri (School of Environmental Engineering, University Malaysia Perlis, 2013)
Research has been done to find alternatives ways to overcome the issues of wasted plastics.